Political Sensitive Design: Raising Public Awareness of Political Money - Urai Panzi; Jagad Aditya Dewantara; Sulistyarini Sulistyarini (JED (Jurnal Etika Demokrasi), 2023)
The urgency of this research is how we as the Society 5.0 generation invite the public to be more sensitive to the law and increase public awareness that financial politics should not be enforced because it can lead to violations of the law and legal practices that should not be carried out. The aim of this research is to determine the awareness of people who do not yet know about money politics. This research uses a qualitative descriptive writing method, namely a writing method used to objectively describe, describe and explain the object of writing. Political Sensibility is a forum for development and understanding for people who are not yet aware of regulations that can harm many people, for example money politics which results in the destruction of democracy. From the problems mentioned above, it is necessary to have a forum as a place for development and understanding for people who are not aware of regulations that can harm many people, for example with the existence of money politics which results in damage to democracy. Increasing Public Awareness Regarding Political Money through Political Sensitive Program Designs.